2003
DOI: 10.1002/mop.10711
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐wavelength Yb‐doped fiber‐ring laser

Abstract: A multi-wavelength ytterbium-doped fiber-ring laser is obtained using a spatial-mode beating filter, placing a section of a G.652 fiber sample into the singleions are easier to realize multi-wavelength laser due to their larger inhomogeneity of gain profile. However, so far results of the multi-wavelength Yb-doped fiber laser have not been reported. In this paper, development of an Yb-doped fiber ring laser with this type of filter is presented. In the ring cavity we use a section of standard single-mode optic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 3 publications
0
16
0
Order By: Relevance
“…Until now there are few reports about multiwavelength Yb-doped fiber. Feng et al realized switchable dual wavelength Yb-doped fiber laser based on few mode fiber grating [6], and Chi et al realized six wavelength Yb fiber laser using a multimode fiber based spatial-mode beating filter [7].The main obstacle to achieve multiwavelength operation at room temperature with a single piece of erbium-doped fiber (EDF) or ytterbium-doped fiber (YDF) is the homogeneous gain broadening [8], which induces strong mode competition and unstable laser output. Therefore to realize simultaneously stable lasing oscillation, the homogeneous broadening should be suppressed.…”
Section: Introductionmentioning
confidence: 99%
“…Until now there are few reports about multiwavelength Yb-doped fiber. Feng et al realized switchable dual wavelength Yb-doped fiber laser based on few mode fiber grating [6], and Chi et al realized six wavelength Yb fiber laser using a multimode fiber based spatial-mode beating filter [7].The main obstacle to achieve multiwavelength operation at room temperature with a single piece of erbium-doped fiber (EDF) or ytterbium-doped fiber (YDF) is the homogeneous gain broadening [8], which induces strong mode competition and unstable laser output. Therefore to realize simultaneously stable lasing oscillation, the homogeneous broadening should be suppressed.…”
Section: Introductionmentioning
confidence: 99%
“…Authors of this paper recently reported a diode-laser pumped compact dual-wavelength Nd:GdVO 4 laser working at 1063 and 1065 nm simultaneously with an output powers of 1 and 4 W, respectively [6]. Pan et al [7] used a Cr 4 + :YAG crystal as a saturable absorber to generate a passively Q-switched dualwavelength Yb-doped fiber laser, which worked at wavelengths 1040 and 1070 nm with a total output power of 4.2 W. Chi et al [8] used a spatial mode-beating filter for wavelength selection and obtained a stable multi-wavelength operation but the output power was only limited to a few mW.…”
Section: Introductionmentioning
confidence: 98%
“…Chi et al realized six-wavelength Yb fiber laser using a multimode fiber based spatial-mode beating filter. 8 But it utilized the rare multimode fiber to constitute the filter. Moghaddam et al demonstrated a multiwavelength YDF laser with up to five lines with a polarization-maintaining fiber (PMF) loop mirror.…”
Section: Introductionmentioning
confidence: 99%